Green supply chain management and environmental performance of firms in the bioenergy sector in Brazil: an exploratory survey - Stefanelli, Nelson Oliveira; Chiappetta Jabbour, Charbel Jose [UNESP]; Lopes de Sousa Jabbour, Ana Beatriz [UNESP] (Elsevier B.V., 2014)
To achieve sustainable development, supply chains must become greener. In this context, the importance of green supply chain management (GSCM) increases because it can contribute to improving firms'environmental performance (EP). However, little is known about these subjects in the context of firms in the bioenergy sector (sugarcane and ethanol production in Brazil). Thus, the objective of this work is to present the results of a survey conducted on 80 micro-, small-, and medium-sized firms that are suppliers in the Brazilian bioenergy sector (sugarcane and ethanol production). These results indicate that GSCM practices strengthen the EP of firms in the sector. Therefore, this article contributes to the existing literature because it addresses the relationship between GSCM and EP in an understudied sector (sugarcane and ethanol production). (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Green supply chain management; Environmental performance; Sustainable supply chain management; Sustainable operations; bioenergy Brazil